(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2025)
The essay traces the history of scholarly reviewing within medieval and Romance studies, from its nineteenth-century origins with Friedrich Diez, Gaston Paris, and Paul Meyer to its twentieth-century transformation through figures such as Gianfranco Contini, Cesare Segre, D’Arco Silvio Avalle, and Alberto Varvaro. It highlights the review’s evolution, its critical and informative functions, and the shifts brought about by historical, methodological, and textual medium changes. The essay concludes with a reflection on the current identity crisis of the review and its prospects.